Completeness of M-fuzzy metric spaces - Amani E. kadhem; Fadhel S. Fadhel (Journal of Madenat Alelem University College, 2009)
In this paper, the definition and basic concepts of M-fuzzy metric is introduced with some of its basic properties and some fundamental results concerning this concept, and then these aspects are used to introduce and prove the completeness of M-fuzzy metric spaces.